PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 5E BERBANTUAN MEDIA LINGKUNGAN TERHADAP KOMPETENSI PENGETAHUAN IPA KELAS IV - Santika Dewi, Ni Putu; Ardana, I Kt; Putra, Made (Universitas Pendidikan Ganesha, 2018)
The aim of this research is to determine the significant differences of knowledge competence of science group of students which is taught by learning model of learning cycle 5E that is supported by environmental media compared with group of students that is taught by conventional learning in fourth grade students of SD Gugus Letkol Wisnu, North Denpasar District, in academic year 2017/2018. The design of this research is a quasi-experimental research with nonequivalent control group design. The population of this research is all the fourth grade students in SD Gugus Letkol Wisnu Sub District of North Denpasar, which is total 332 students that spread in 9 classes. The sample determination was done by random sampling technique. The sample in this research is the students of grade IV A SDN 1 Peguyangan with 43 students as experiment group and fourth grade students of SDN 12 Peguyangan with 41 students as control group. The data were collected by using the test method in the form of a standard multiple-choice objective test. The data obtained were analyzed using the t-test. Based on the results of data analysis obtained thitung = 4,453 while at the level of significance 5% and dk = 82 obtained ttable value = 1,989 so thitung = 4,453 > ttable = 1,989. Based on the test criteria, Ho is rejected. The average score of science knowledge competence in the group that was taught by the Learning Cycle 5E model with the help of environmental media was 81,53, while in the group taught by conventional learning was 72,82. Based on the result, it can be concluded that there is influence of Learning Cycle 5E model with the help of environmental media on science knowledge competence of fourth grade students of SD Gugus Letkol Wisnu Sub-district of North Denpasar in academic year 2017/2018 Keywords : Learning Cycle 5E, environmental, knowledge competence of science